Ответ:
4.8
1) (√15 + 3√5)² - 30√3 =
(√15)² + 2(√15)(3√5) + (3√5)² =
15 + 6√75 + 9 * 5 - 30√3 =
15 + 45 + 6√(25 * 3) - 30√3 =
60 + 6 * 5 * √3 - 30√3 =
60 + 30√3 - 30√3 = 60
2) (√(4 - √7) + √(√7 + 4))² =
(√(4 - √7))² + 2(√(4 - √7))(√(√7 + 4)) + (√(√7 + 4))² =
4 - √7 + 2√((4 - √7)(√7 + 4)) + √7 + 4 =
8 + 2√((4 - √7)(4 + √7)) =
8 + 2√(4² - (√7)²) =
8 + 2√(16 - 7) =
8 + 2√9 =
8 + 2 * 3 =
8 + 6 = 14
3) (√(5 - 2√6) + √(5 + 2√6))² =
(√(5 - 2√6))² + 2(√(5 + 2√6))(√(5 - 2√6)) + (√(5 + 2√6))² =
5 - 2√6 + 2(√(5² - (2√6)²)) + 5 + 2√6 =
10 + 2(√(25 - 4 * 6)) =
10 + 2(√(25 - 24)) =
10 + 2√1 =
10 + 2 * 1 =
10 + 2 = 12
4) (√(6 + √11) - √(6 - √11))² =
(√(6 + √11))² - 2(√(6 + √11))(√(6 - √11)) + (√(6 - √11))² =
6 + √11 - 2(√(6² - (√11)²)) + 6 - √11 =
12 - 2(√(36 - 11)) =
12 - 2√25 =
12 - 2 * 5 =
12 - 10 = 2
4.9
1) (2 - √a)(2 + √a) - 4 =
4 - (√a)² - 4 =
0 - a = -a
2) (3 - √2a)(3 + √2a) + 4a =
9 - (√2a)² + 4a =
9 - 2a + 4a = 9 + 2a
3) (2√3 - 3√a)(2√3 + 3√a) =
(2√3)² - (3√a)² =
4 * 3 - 3 * a = 12 - 3a
4) (2√7 - √7a)(2√7 + √7a) =
(2√7)² - (√7a)² =
4 * 7 - 7a = 28 - 7a
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
4.8
1) (√15 + 3√5)² - 30√3 =
(√15)² + 2(√15)(3√5) + (3√5)² =
15 + 6√75 + 9 * 5 - 30√3 =
15 + 45 + 6√(25 * 3) - 30√3 =
60 + 6 * 5 * √3 - 30√3 =
60 + 30√3 - 30√3 = 60
2) (√(4 - √7) + √(√7 + 4))² =
(√(4 - √7))² + 2(√(4 - √7))(√(√7 + 4)) + (√(√7 + 4))² =
4 - √7 + 2√((4 - √7)(√7 + 4)) + √7 + 4 =
8 + 2√((4 - √7)(4 + √7)) =
8 + 2√(4² - (√7)²) =
8 + 2√(16 - 7) =
8 + 2√9 =
8 + 2 * 3 =
8 + 6 = 14
3) (√(5 - 2√6) + √(5 + 2√6))² =
(√(5 - 2√6))² + 2(√(5 + 2√6))(√(5 - 2√6)) + (√(5 + 2√6))² =
5 - 2√6 + 2(√(5² - (2√6)²)) + 5 + 2√6 =
10 + 2(√(25 - 4 * 6)) =
10 + 2(√(25 - 24)) =
10 + 2√1 =
10 + 2 * 1 =
10 + 2 = 12
4) (√(6 + √11) - √(6 - √11))² =
(√(6 + √11))² - 2(√(6 + √11))(√(6 - √11)) + (√(6 - √11))² =
6 + √11 - 2(√(6² - (√11)²)) + 6 - √11 =
12 - 2(√(36 - 11)) =
12 - 2√25 =
12 - 2 * 5 =
12 - 10 = 2
4.9
1) (2 - √a)(2 + √a) - 4 =
4 - (√a)² - 4 =
0 - a = -a
2) (3 - √2a)(3 + √2a) + 4a =
9 - (√2a)² + 4a =
9 - 2a + 4a = 9 + 2a
3) (2√3 - 3√a)(2√3 + 3√a) =
(2√3)² - (3√a)² =
4 * 3 - 3 * a = 12 - 3a
4) (2√7 - √7a)(2√7 + √7a) =
(2√7)² - (√7a)² =
4 * 7 - 7a = 28 - 7a